KONSEP PENGGAJIAN, TUNJANGAN DAN KOMPENSASI DALAM MANAJEMEN SUMBER DAYA MANUSIA PADA PENDIDIKAN ISLAM - Nofiyanti, Dita; Umma, Siti Rosyidatul; Khoirunnisa’, Syabilananta; Mardiyah, Mardiyah (Jurnal Manajemen Pendidikan, 2025)
Objective: This article discusses the management of compensation, salary, and allowance systems for educators in Islamic educational institutions with the aim of improving their welfare and motivation, enabling them to provide quality educational services in accordance with Islamic teachings. This research uses a literature review and policy analysis approach to examine the application of the principles of justice ('adl), balance (tawazun), and responsibility (mas'uliyah) in human resource management. The primary objective is to identify challenges and formulate effective solutions for building a fair, transparent, and sustainable payroll system. The study's results demonstrate the importance of improving the professionalism of human resource management through the use of information technology and training programs for administrators. By implementing a sound payroll system, Islamic educational institutions are expected to strengthen educational quality, maintain institutional stability, and optimally encourage the motivation and loyalty of educators.